Perancangan Sistem Informasi Pendaftaran Online Santri Baru Pondok Pesantren Al-Inaayah Berbasis Web - Fikri Miftahul Falah; Kecitaan Harefa (CV. Multi Kreasi Media, 2022)
Pondok Pesantren Al-Inaayah is a school that provides boarding schools that focus on education, especially in the field of Islamic religious education. From year to year, the number of prospective new students always increases. For now, the registration process for new students is still using the manual system by registering directly at the Islamic boarding school. In an era that is increasingly developing today, the registration process can actually be done without having to come directly to the cottage, so that it can make it easier for parents or prospective students to register new students more quickly and effectively. Based on this, an online registration information system was designed for web-based acceptance of new students and for the analysis and design stages using the waterfall method. With the design of the system, it can make it easier for the registration process for new students, data storage relating to the admission of new students can be stored neatly using a database and information relating to the acceptance of new students can be obtained accurately and accurately as consideration in making a decision.